Digital Transformation in Arabic Language Education in Pakistan: A Multi-Level Analysis of Policy, Institutional Capacity, and Pedagogical Practices - Manzoor Ahmed Kalwar; Najmul Sahar Ilyas; Bashir Ahmed Kalwar; Danyal Ahmad; Abdul Rasheed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This paper discusses the digital revolution in Arabic language education in Pakistan through a combined review of national policy frameworks, institutional capacity, and pedagogical practices. The study examines the national education policies, Higher Education Commission (HEC) guidelines, and the Arabic language curriculum of the selected universities using a qualitative document analysis approach. The results indicate a vast difference between the policy aspirations and the reality. Although digital integration is strongly encouraged within national frameworks, its implementation in Arabic language programs remains uneven and largely confined to the use of simple technologies. Institutional capacity, faculty digital competence, and traditional disciplinary traditions are major influences on pedagogical practices. The paper proposes that digital transformation in Arabic language education is largely symbolic, lacking coordination with institutional strategies and substantial pedagogical change. This study can contribute to the existing scarcity of research on digital Arabic learning in South Asia and suggest useful policy, institutional, and pedagogical implications to policymakers, universities, and teachers.